Reforming the Capital Maintenance Doctrine in the Context of China:: From the Guiding Cases Perspective - Fei, Gao (Journal of Malaysian and Comparative Law, 2020)
The doctrine of capital maintenance is an important principle of company law. Since the 20th century, a number of crucial changes relating to the rules of capital maintenance have been adopted in several jurisdictions. This has resulted in the deregulation and relaxation of a number of measures. China has followed this trend and has relaxed the regulations on corporate capital in recent years. However, the rules on capital maintenance have remained largely unchanged. This has elicited a heated debate on whether China should abolish the doctrine of capital maintenance altogether. This article argues that instead of abolishing the capital maintenance doctrine, it should be modified to make creditor protection more effective. The article suggests that, the guiding cases released by the PRC Supreme People’s Court play an important role in the development of company law in China, and there are influential cases in modifying the rules of capital maintainance. The paper also suggests that the mandatory capital maintenance rules under Chinese company law should be further relaxed. The court should not mechanically follow existing capital maintenance rules but should improve it through guiding cases.